La0.67Ce0.03Sr0.3MnO3-coupled microwave assisted ultra-fast synthesis of nanocrystalline cobalt oxide and Bismuth oxide - Rajagopal, Rajashree; Mona, J.; Joshi, Rakesh S.; Kale, Sangeeta N.; Pradhan, Sivararn; Gaikwad, A. B.; Ravi, V. (Materials Letters, 2008)
Bismuth hydroxide and Cobalt hydroxide gels were freshly prepared by adding aqueous sodium hydroxide to their corresponding nitrates under basic conditions. Then they were oven dried at 373 K and found to be amorphous in X-ray diffraction (XRD) study. They crystallized into their respective oxides by microwave irradiation (2.45 GHz) in merely 2 min using La0.67Ce0.03Sr0.3MnO3 (LCSMO) as couplant in a microwave domestic oven (similar to 100 W). This is the lowest temperature treatment and synthesis time so far reported in the literature for the formation of these systems. Formation of nanocrystallites of Bi2O3 (10 nm) and Co3O4 (15 nm) has been confirmed by XRD. Normally these hydroxides produce oxides only on heating at temperature >673 K or digesting them at 373 K for 4 - 6 hours as reported by us earlier. Microwave assisted heating proves to be a novel technology whose applications can be carefully harnessed due to its unique effects compared to the conventional heating, such as rapid volumetric heating, shortened reaction time and energy saving. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Citrate gel method; Manganites; Microwave; Oxides

Microwave assisted low temperature rapid synthesis of manganite system using La0.67Ce0.03Sr0.3MnO3 mini-cavity furnace - Kale, Sangeeta N.; Rajagopal, Rajashree; Mona, J.; Londhe, D. P.; Joshi, Rakesh S.; Jagadale, Tushar C.; Satyanarayana, C.; Ravi, V. (Materials Letters, 2008)
Amorphous La0.7Sr0.3MnO3 (LSMO) and La0.7Ca0.3MnO3 (LCMO) precursor powders synthesized by the citrate gel method at 673 K, have been found to crystallize by microwave irradiation in just 60 s using La0.67Ce0.03Sr0.3MnO3 (Ce-LSMO) as couplant. This is the lowest temperature treatment and synthesis time so far reported in literature for the fort-nation of manganite systems. Using ceramic route, the same amorphous samples crystallize on heat treatment only at temperatures greater than 1000 K. The microwave heating through this method is novel and has tremendous potential for accelerating the evolution of the product phase in very shorter durations, with just low temperature processing of the precursors, which cannot be realized in normal process. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Citrate gel method; LSMO; Manganites; Microwave; Oxides

Ferromagnetic to spin glass cross over in (La,Tb)(2/3)Ca1/3MnO3 - Sankar, C. Raj; Vijayanand, S.; Joy, Pattayil Alias (Solid State Sciences, 2009)
In the series La2/3-xTbxCa1/3MnO3, it is known that the compositions are ferromagnetic for smaller values of x and show spin glass characteristics at larger values of x. Our studies on the magnetic properties of various compositions in the La2/3-xTbxCa1/3MnO3 series show that the cross over from ferromagnetic to spin glass region takes place above x approximate to 1/8. Also, a low temperature anomaly at 30 K, observed in the ac susceptibility curves, disappears for compositions above this critical value of x. A mixed phase region coexists in the narrow compositional range 0.1 <= x <= 0.125, indicating that the ferromagnetic to spin glass cross over is not abrupt. (C) 2008 Elsevier Masson SAS. All rights reserved.
Keywords: Ferromagnetism; Magnetic clusters; Manganites; perovskite; Spin glass